Design and Synthesis of Conducting Polymer Bio-Based Polyurethane Produced from Palm Kernel Oil - Muhammad Abdurrahman Munir; Khairiah Haji Badri; Lee Yook Heng; Ahlam Inayatullah; Hamid Alkhair Badrul; Emelda Emelda; Eliza Dwinta; Nurul Kusumawardani; Ari Susiana Wulandari; Veriani Aprilia; Rachmad Bagas Yahya Supriyono (International Journal of Polymer Science)
Polyurethane (PU) is a unique polymer that has versatile processing methods and mechanical properties upon the inclusion of selected additives. In this study, a freestanding bio-based polyurethane film the screen-printed electrode (SPE) was prepared by the solution casting technique, using acetone as solvent. It was a one-pot synthesis between major reactants, namely, palm kernel oil-based polyol and 4,4-methylene diisocyanate. The PU has strong adhesion on the SPE surface. The synthesized bio-based polyurethane was characterized using thermogravimetry analysis, differential scanning calorimetry, Fourier-transform infrared spectroscopy (FTIR), surface area analysis by field emission scanning electron microscope, and cyclic voltammetry. Cyclic voltammetry was employed to study electrocatalytic properties of SPE-polyurethane towards oxidation of PU. Remarkably, SPE-PU exhibited improved anodic peak current as compared to SPE itself using the differential pulse voltammetry method. Furthermore, the formation of urethane linkages (-NHC(O) backbone) after polymerization was analyzed using FTIR and confirmed by the absence of peak at 2241 cm-1 attributed to the sp-hydridized carbons atoms of C≡C bonds. The glass transition temperature of the polyurethane was detected at 78.1°C.